2012
DOI: 10.1016/j.neuroimage.2012.03.024
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral significance of coherent resting-state oscillations after stroke

Abstract: Stroke lesions induce not only loss of local neural function, but disruptions in spatially distributed areas. However, it is unknown whether they affect the synchrony of electrical oscillations in neural networks and if changes in network coherence are associated with neurological deficits. This study assessed these questions in a population of patients with subacute, unilateral, ischemic stroke.Spontaneous cortical oscillations were reconstructed from high-resolution electroencephalograms (EEG) with adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
164
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(185 citation statements)
references
References 70 publications
18
164
3
Order By: Relevance
“…Connectivity measures were lower in patients than in controls in the alpha and beta frequency bands, but not in the delta frequency band. This is in line with the notion of coherence of resting state oscillations in the alpha band, but not in lower frequencies, being associated with cognitive and motor functioning [12, 25]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Connectivity measures were lower in patients than in controls in the alpha and beta frequency bands, but not in the delta frequency band. This is in line with the notion of coherence of resting state oscillations in the alpha band, but not in lower frequencies, being associated with cognitive and motor functioning [12, 25]. …”
Section: Discussionsupporting
confidence: 89%
“…For example, interhemispheric spectral asymmetry in the 0.5–25 Hz range estimated with the Brain Symmetry Index predicted that outcome and treatment effect [7, 8], whole brain partial least square models for delta power correlated with the severity of neurological deficit [9], and ipsilateral motor cortex connectivity were associated with effects of physical therapy [10]. In studies with high density arrays, various measures of functional connectivity revealed changes in both ipsi- and contralateral hemisphere that were related to functional recovery [11, 12]. Others have focused on interhemispheric connectivity, for example with TMS-EEG paradigms [13].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, signals in the damaged and undamaged hemispheres might undergo hemisphere-specific changes that reduce their correlation. EEG signals (power, coherence) are abnormal both within and across hemispheres poststroke, and correlate with behavioral impairment (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Such source connectivity analyses have revealed that focal lesions and diffuse neurodegeneration are associated with a disruption of alpha-band coherence between clinically dysfunctional brain areas and the rest of the brain (Fig. 3) (Dubovik et al, 2013(Dubovik et al, , 2012Guggisberg et al, 2008b). Moreover, local decreases in alpha-band coherence between a given brain area and the rest of the brain are linearly correlated with neurological deficits.…”
Section: Electroencephalographymentioning
confidence: 98%